Mekanisme Fitoremediasi: Review - Geo Aghni Bintang Sukono; Farhan Rahmatullah Hikmawan; Evitasari; Dodi Satriawan (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2020)
Increasing urbanization, overpopulation, and industrialization are amongst the major lead of environmental degradation and pollution. Severe metals like Pb, Zn, Cd, As, etc. are among the highly harmful pollutants which fair harmful effects on all existing things. Lead is a pollutant that interferes with the food chain and is deadly even at low sedimentation. The purification technique used to wipe contaminants from wastewater is not only very scarce but also leads to a negative effect on the ecosystem. Phytoremediation, an environmentally friendly technique that is both ecologically and economically impression, is an appealing alternative to influx methods which are very scarce. Phytoremediation is an in-situ remediation technique that uses the inherent capability of living crops. Phytoremediation uses crops to clean up contaminants in the environment. Crops can help cleanse many types of contaminants including metals, pesticides, detonators, and oils. There are three ways in which crops can sway the mass of pollution in soil, sediment, water, and air. The first is phytoextraction also called phytoaccumulas, which refers to the uptake and translocation of metal contaminants in the soil by plant roots to above-ground plant parts. The second rizofiltration is mainly used to improve extracted groundwater, surface water, and low- contaminant wastewater. And the third is phytovolatilization which involves using plants to take contaminants from the soil, visit them into easy forms and transfer them to the atmosphere.